Gemcitabine and oxaliplatin with or without cetuximab in advanced biliary-tract cancer (BINGO): a randomised, open-label, non-comparative phase 2 trial - Malka, David; Herrmann, Thomas (The lancet. Oncology, 2014)
Background - Gemcitabine plus a platinum-based agent (eg, cisplatin or oxaliplatin) is the standard of care for advanced biliary cancers. We investigated the addition of cetuximab to chemotherapy in patients with advanced biliary cancers. - Methods - In this non-comparative, open-label, randomised phase 2 trial, we recruited patients with locally advanced (non-resectable) or metastatic cholangiocarcinoma, gallbladder carcinoma, or ampullary carcinoma and a WHO performance status of 0 or 1 from 18 hospitals across France and Germany. Eligible patients were randomly assigned (1:1) centrally with a minimisation procedure to first-line treatment with gemcitabine (1000 mg/m2) and oxaliplatin (100 mg/m2) with or without cetuximab (500 mg/m2), repeated every 2 weeks until disease progression or unacceptable toxicity. Randomisation was stratified by centre, primary site of disease, disease stage, and previous treatment with curative intent or adjuvant therapy. Investigators who assessed treatment response were not masked to group assignment. The primary endpoint was the proportion of patients who were progression-free at 4 months, analysed by intention to treat. This study is registered with ClinicalTrials.gov, number NCT00552149. - Findings - Between Oct 10, 2007, and Dec 18, 2009, 76 patients were assigned to chemotherapy plus cetuximab and 74 to chemotherapy alone. 48 (63%; 95% CI 52-74) patients assigned to chemotherapy plus cetuximab and 40 (54%; 43-65) assigned to chemotherapy alone were progression-free at 4 months. Median progression-free survival was 6·1 months (95% CI 5·1-7·6) in the chemotherapy plus cetuximab group and 5·5 months (3·7-6·6) in the chemotherapy alone group. Median overall survival was 11·0 months (9·1-13·7) in the chemotherapy plus cetuximab group and 12·4 months (8·6-16·0) in the chemotherapy alone group. The most common grade 3-4 adverse events were peripheral neuropathy (in 18 [24%] of 76 patients who received chemotherapy plus cetuximab vs ten [15%] of 68 who received chemotherapy alone), neutropenia (17 [22%] vs 11 [16%]), and increased aminotransferase concentrations (17 [22%] vs ten [15%]). 70 serious adverse events were reported in 39 (51%) of 76 patients who received chemotherapy plus cetuximab (34 events in 19 [25%] patients were treatment-related), whereas 41 serious adverse events were reported in 25 (35%) of 71 patients who received chemotherapy alone (20 events in 12 [17%] patients were treatment-related). One patient died of atypical pneumonia related to treatment in the chemotherapy alone group. - Interpretation - The addition of cetuximab to gemcitabine and oxaliplatin did not seem to enhance the activity of chemotherapy in patients with advanced biliary cancer, although it was well tolerated. Gemcitabine and platinum-based combination should remain the standard treatment option. - Funding - Institut National du Cancer, Merck Serono.